Clinical implications of gastrointestinal symptoms in systemic amyloidosis. Issue 4 (10th October 2017) - Yen, T.; Chen, F. W.; Witteles, R. M.; Liedtke, M.; Nguyen, L. A.
Abstract: Background: Gastrointestinal (GI) symptoms in systemic amyloidosis patients are poorly characterized. This purpose of this study is to define the epidemiology and clinical implications of such symptoms. Methods: This was a retrospective cohort study of 583 amyloid patients seen at a tertiary referral center. Of 96 symptomatic patients, 82 received endoscopic biopsies, subsequently grouped into those with histologic evidence of GI amyloid (biopsy proven) vs without (biopsy absent). Key Results: 16.8% of patients had GI symptoms, and had more abnormal NT‐proBNP, cardiac ejection fraction, serum albumin, and alkaline phosphatase ( P  < .01). Of those who received endoscopy, the sites of highest diagnostic yield were stomach, duodenum and colon. The most common symptom was abdominal pain, nausea, or vomiting (50.0%). Of the symptomatic patients, only 37 (45%) had biopsy proven GI amyloid. Biopsy proven patients more often had cardiac involvement ( P  < .005), and more often received hematologic therapy or transplant ( P  = .01). Biopsy absent patients had more frequent neurologic involvement ( P  = .17). Biopsy status had no significant correlation with other indicators of amyloid burden, GI symptoms or management. Conclusions & Inferences: Nearly one in six amyloid patients have GI symptoms, and half do not have GI amyloid. The type of symptom does not predict endoscopic findings. Most biopsy absent patients are not managed as a functional disorder despite no alternative etiology. Gastroenterologists may have an increased role to play in the care of systemic amyloidosis beyond performing endoscopies, such as evaluating cardiac amyloid patients for concurrent GI amyloid. Abstract : Gastrointestinal symptoms in amyloid patients are assumed to represent mucosal amyloid deposition, because there is little known about functional bowel disorders and dysmotility in amyloidosis. We found that these symptoms are not uncommon, but many symptomatic patients have no demonstrable etiology for these symptoms. Those with GI amyloid more likely have cardiac amyloid, suggesting that gastroenterologists have more of a role to play in systemic amyloidosis.